Ongoing Research on Microgreens Nutritional Properties, Shelf-life, Sustainable Production, Innovative Growing and Processing Approaches - Paradiso, Vito Michele; Renna, Massimiliano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Microgreens garner immense potential for improving the nutrition of the human diet, considering their high content of healthy compounds. On the other hand, they are becoming known not only for their nutritional value but also for their interesting organoleptic traits and commercial potential. In this Special Issue we aim to publish high-quality research papers covering the state-of-the-art, recent progress and perspectives related to production, post-harvest, characterization, and the potential of microgreens. A broad range of aspects such as cultivation, post-harvest techniques and packaging, analytical methods, nutritional value, bioaccessibility and prospects are covered. All contributions are of great significance and could stimulate further research in this area.